Intruding into a conversation: how behavioral manipulation could support management of Xylella fastidiosa and its insect vectors - Sabina Avosani; Rachele Nieri; Valerio Mazzoni; Gianfranco Anfora; Zeinab Hamouche; Caterina Zippari; Maria Luisa Vitale; Vincenzo Verrastro; Eustachio Tarasco; Ilaria D’Isita; Salvatore Germinara; Thomas F. Döring; et al. (Journal of Pest Science, 2024)
Behavioral manipulation (BM) is a multimodal control approach based on the interference with the stimuli mediating insect perception and interaction with the surroundings. BM could represent a win–win strategy for the management of vector-borne plant pathogens as the bacterium Xylella fastidiosa , since it could reduce the number of vectors alighting on host plants and, consequently, the chances for transmission to occur. In this review, we summarized current knowledge and highlighted gaps in information on (i) how insect vectors of X. fastidiosa in general, and more specifically the meadow spittlebug Philaenus spumarius , locate and accept the host plant ; and (ii) how behavioral manipulation techniques could be applied to disrupt the vector–host plant interaction. Finally, we discussed how diverse BM strategies could be combined with other integrated pest management tools to protect olive groves from inoculation with the fastidious bacterium.